2020
DOI: 10.1111/ppc.12451
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of depression with neglect and abuse in individuals over 65 years of age

Abstract: Purpose: This study was conducted to evaluate the correlation of neglect and abuse with depression in individuals over 65 years of age.Design and Methods: This descriptive study included 290 elderly people who were registered at 10 family health centers in Turkey.Findings: It was determined that mental health problems were present in the sample, and elderly individuals were exposed to abuse and neglect. The levels of depression were found to be high in elderly individuals with no spouses, low level of educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…In this process, individuals constantly question the meaning of life, their expectations from life, their capacity to cope with life's challenges and their ability to connect with those who are close to them. Given that old age affects an individual's life purpose and plans, rearranging the individual's life goals and expectations is thus necessary 12 . Needless to say, this situation affects the morale as well as the physical and psychological well‐being of the elderly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, individuals constantly question the meaning of life, their expectations from life, their capacity to cope with life's challenges and their ability to connect with those who are close to them. Given that old age affects an individual's life purpose and plans, rearranging the individual's life goals and expectations is thus necessary 12 . Needless to say, this situation affects the morale as well as the physical and psychological well‐being of the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Given that old age affects an individual's life purpose and plans, rearranging the individual's life goals and expectations is thus necessary. 12 Needless to say, this situation affects the morale as well as the physical and psychological well-being of the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…However, Çakmur (2015), while confirming a higher prevalence of frailty in rural areas, found no significant gender effects [31]. On the other hand, the gender differences in health status at old age, with women reporting worse health indicators, were reported in several studies specific to Turkey's different regions [32,33]. Several studies showed poverty and low educational attainment to have significant adverse effects on older people's health status and quality of life [30,31,[33][34][35].…”
Section: Population Ageing In Turkeymentioning
confidence: 99%
“…On the other hand, the gender differences in health status at old age, with women reporting worse health indicators, were reported in several studies specific to Turkey's different regions [32,33]. Several studies showed poverty and low educational attainment to have significant adverse effects on older people's health status and quality of life [30,31,[33][34][35]. These differentials appear more pronounced among highly disadvantaged groups of older people, such as in-prison populations [36].…”
Section: Population Ageing In Turkeymentioning
confidence: 99%
See 1 more Smart Citation